Evaluation of Rapid SARS-CoV-2 Antigen Detection as a Single Diagnostic Test and When Combined with C-Reactive Protein Level or Neutrophil to Lymphocyte Ratio in Suspected COVID-19 Subjects - Mashaly, Mervat; El-Emshaty, Wafaa M.; Saudy, Niveen; El-Deeb, Douaa R. (Journal of laboratory physicians, 2022)
Abstract Background Rapid antigen detection tests of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) play a crucial role in the control of the current coronavirus disease 2019 (COVID-19) pandemic. Data about the real diagnostic performance of such tests is still insufficient and hence their evaluation is of high priority. Objectives The aim of this study was to evaluate the diagnostic performance of BIOCREDIT COVID-19 antigen test alone and in combination with either C-reactive protein (CRP) or neutrophil/lymphocyte ratio (NLR) in comparison to real-time quantitative polymerase chain reaction (RT-qPCR). Additionally, we investigated the selection criteria of the suspect for best performance of the antigen test. Materials and Methods Paired nasopharyngeal (NP) swabs were collected from 200 suspected COVID-19 subjects for SARS-CoV-2 RNA by RT-qPCR and for antigen detection by BIOCREDIT test. Simultaneously, for all suspect, clinical presentations were recorded as well as CRP level and NLR were determined. Results Among 200 tested NP swabs, 125 (62.5%) were RT-PCR positive. Overall sensitivity, specificity and accuracy of BIOCREDIT test were 34.4, 98.7, and 58.5%, respectively. Sensitivity of the BIOCREDIT test was higher in COVID-19 suspect, with high viral load (100%), severely ill (56.2%), with fever alone (40%), elevated CRP (41.1%), and high NLR (36.2%). In combination with NLR or CRP, sensitivity of BIOCREDIT test increased to 89.4 and 81.6%, respectively, while its specificity decreased to 67 and 59%, respectively. Conclusion The overall low sensitivity of BIOCREDIT/COVID-19 antigen test does not permit its use as a single diagnostic test for COVID-19. However, its use should be restricted only if it is combined with either CRP or NLR in suspect with certain criteria.